1994
DOI: 10.1002/bjs.1800810325
|View full text |Cite
|
Sign up to set email alerts
|

Influence of epidermal growth factor and interferon γ on healing of oesophageal corrosive burns in the rat

Abstract: A study was performed to attempt to modify the healing response to severe oesophageal corrosive burns to prevent complications. The study was performed on four groups each of 15 Wistar rats: a control group, an untreated group and groups given epidermal growth factor (EGF) alone or EGF for 5 days and interferon (IFN) gamma from the sixth to 20th day. In the last three groups an oesophageal lesion was induced with 2.5 mol l-1 sodium hydroxide solution. The efficacy of treatment was assessed on days 2, 5 and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 20 publications
0
29
0
3
Order By: Relevance
“…Pharmacological agents such as steroids, penicillamine, heparin, indomethacin, epidermal growth factor, gamma interferon, N-acetylcysteine, estrogen, progesterone, antibiotics, and their combinations are used to suppress inflammation and collagen synthesis, and to prevent fibroplasia and stricture formation. Despite the decrease in stricture formation in these experimental studies, the rate of stricture formation seen in advanced-grade corrosive esophagitis is still 70-100% (6)(7)(8)(14)(15)(16)(17)(18)(19)(20). Although the experimental studies have documented the efficiency of multiple agents, the current treatment protocol in corrosive esophagitis is still restricted to steroid, antibiotics and neutralization of the caustic agent in the early phase (13,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological agents such as steroids, penicillamine, heparin, indomethacin, epidermal growth factor, gamma interferon, N-acetylcysteine, estrogen, progesterone, antibiotics, and their combinations are used to suppress inflammation and collagen synthesis, and to prevent fibroplasia and stricture formation. Despite the decrease in stricture formation in these experimental studies, the rate of stricture formation seen in advanced-grade corrosive esophagitis is still 70-100% (6)(7)(8)(14)(15)(16)(17)(18)(19)(20). Although the experimental studies have documented the efficiency of multiple agents, the current treatment protocol in corrosive esophagitis is still restricted to steroid, antibiotics and neutralization of the caustic agent in the early phase (13,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Although in most of the similar experimental studies, lye has been used, there are different opinions about the amount, concentration and duration of the caustic agent [3,[13][14][15]. Ingestions of alkaline solutions with a pH of less than 11.5 are considered relatively safe, whereas those with a pH exceeding this level may produce acute perforation and death or, more typically, esophageal stenosis and significant morbidity [1,13,16,17]. Solid lye substances tend to lodge in the oropharynx or upper esophagus, whereas concentrated liquid caustics cause damage to the distal esophagus and stomach [14].…”
Section: Discussionmentioning
confidence: 99%
“…In control animals, illumination was performed at 3 h. Four rats in each group were sacrificed at 48 h after illumination to study the acute effects, as a pilot study had shown a maximum PDT effect at 48 h. The other four rats in each group were sacrificed on day 28 after illumination to study healing because, by then, a pilot study had shown complete re-epithelialization. Furthermore, that time interval was found to show full expression of stenosis after oesophageal corrosive burns (Berthet et al, 1994).…”
mentioning
confidence: 83%